Mathematics problem solving assessment test / Haslizatul Fairuz Mohamed Hanum and Nor Zulihaz Zulkiffli - Mohamed Hanum, Haslizatul Fairuz; Zulkiffli, Nor Zulihaz
Evaluation of students programming skills involves various measures including mathematical problem solving skill. The Mathematics Problem Solving Assessment Test (MPSAT) attempts to help students and lecturers of introductory programming courses to evaluate student's mathematics problem solving skills prior and after attending an introductory programming course. Offering a single-time registration and quick assessment, development of MPSAT has considered various aspects including the type of questions, timing of assessment, scoring guide and the development method. MPSAT is written for Windows platform using PHP and Javascript. The preliminary test and post test, each consists of 40 questions are intelligently selected from the database.